Morphological estimation of changes in cancellous raduis bone for forensic age determination - S. A. Fominykh; V. E. Yankovskiy; Y. A. Vysotskiy; G. N. Borodina (Acta Biomedica Scientifica, 2015)
Visual researches showed that the cancellous bone of the distal radius has significant morphological changes with the increase of years. Revealed structural changes of cancellous bone allows to differentiate the age of an object and to direct a medical expert towards the proposed age group at the identification study. As a result of photocolorimetric research of involution changes of cancellous bone of the distal radius we found statistically significant increase of light transmission with the increase of years which is associated with an increase of osteoporosis. The correlation coefficient ranged from 0,63 to 0,80. On the basis of these data mathematical models that allow to determine the person's age in the forensic identification researches of the distal radius were developed (standard mean square error in determination of the age was from 6,6 to 8,2 years).